A prologue to nostalgia: savouring creates nostalgic memories that foster optimism. Issue 3 (3rd April 2019) - Biskas, Marios; Cheung, Wing-Yee; Juhl, Jacob; Sedikides, Constantine; Wildschut, Tim; Hepper, Erica
ABSTRACT: How are nostalgic memories created? We considered savouring as one process involved in the genesis of nostalgia. Whereas nostalgia refers to an emotional reflection upon past experiences, savouring is a process in which individuals deeply attend to and consciously capture a present experience for subsequent reflection. Thus, having savoured an experience may increase the likelihood that it will later be reflected upon nostalgically. Additionally, to examine how cognitive and emotional processes are linked across time, we tested whether nostalgia for a previously savoured experience predicts optimism for the future. Retrospective reports of having savoured a positive event were associated with greater nostalgia for the event (Study 1). Retrospective reports of savouring a time period (college) were associated with greater nostalgia for that time period when participants were in a setting (alumni reunion event) that prompted thoughts of the time period (Study 2). Savouring an experience predicted nostalgia for the experience 4–9 months later (Study 3). Additionally, nostalgia was associated with greater optimism (Studies 2-3). Thus, savouring provides a foundation for nostalgic memories and an ensuing optimism.